The diagnostic value of salivary cortisol and salivary cortisone in patients with suspected hypercortisolism - Berndt, Vendela; Dahlqvist, Per; de Verdier, Jennie; Ryberg, Henrik; Ragnarsson, Oskar (Frontiers in Endocrinology, 2022)
Background Diagnosing endogenous hypercortisolism remains a challenge, partly due to a lack of biochemical tests with good diagnostic accuracy. Objectives To evaluate the diagnostic value of salivary cortisol and cortisone in patients with suspected hypercortisolism. Methods Retrospective study including 155 patients with adrenal incidentaloma, and 54 patients with suspected Cushing´s syndrome (CS). Salivary samples were collected at home, at 11 p.m., and at 8 a.m. following an over-night dexamethasone suppression test (DST). Salivary cortisol and cortisone were measured with liquid chromatography-tandem mass spectrometry. Results Ten of 155 patients with adrenal incidentaloma were considered to have autonomous cortisol secretion (ACS). Using previously established cut-offs, all patients with ACS had elevated plasma-cortisol (>50 nmol/L) following DST, 9/10 had elevated late-night salivary cortisone (>15 nmol/L) whereas only 4/10 had elevated late-night salivary cortisol (LNSC; >3 nmol/L) compared to 35%, 9% and 8%, respectively, of the 145 patients with non-functioning adrenal incidentaloma. Six (60%) patents with ACS had elevated salivary cortisol and cortisone at 8 a.m. following DST compared to 9% and 8%, respectively, of patients with non-functioning adrenal incidentaloma. One of 6 patients with overt CS had a normal LNSC and one had normal late-night salivary cortisone, while all had increased salivary cortisol and cortisone following DST. Conclusion LNSC is not sufficiently sensitive or specific to be used for screening patients with suspected hypercortisolism. Instead, late-night salivary cortisone seems to be a promising alternative in patients with adrenal incidentaloma and salivary cortisone at 8 a.m. following DST in patients with suspected CS. Larger studies are needed to confirm these findings.